Core psychiatry - Wright, Padraig; Stern, Julian; Phelan, Michael (Saunders Elsevier, 2012)
A new edition of the BMA award winning textbook for trainee psychiatrists, covering in one concise volume all the subjects required for success in the new MRCPsych and similar exam. Written in highly engaging manner, it will also prove invaluable to qualified psychiatrists who need to keep up-to-date with all the latest development, as well as clinical psychologists, general practitioners, psychiatric nurses and senior medical students